What sequencing technologies can teach us about innate immunity. Issue 1 (7th November 2021) - Mohammed Salih, Mays; Carpenter, Susan
Abstract: For years, we have taken a reductionist approach to understanding gene regulation through the study of one gene in one cell at a time. While this approach has been fruitful it is laborious and fails to provide a global picture of what is occurring in complex situations involving tightly coordinated immune responses. The emergence of whole‐genome techniques provides a system‐level view of a response and can provide a plethora of information on events occurring in a cell from gene expression changes to splicing changes and chemical modifications. As with any technology, this often results in more questions than answers, but this wealth of knowledge is providing us with an unprecedented view of what occurs inside our cells during an immune response. In this review, we will discuss the current RNA‐sequencing technologies and what they are helping us learn about the innate immune system.